Effect of management practices on yield components and swelling factor of Plantago indica: a medicinal plant - DAS, MANISH (The Indian Journal of Agricultural Sciences, 2014)
An investigation was carried out to study the impact of sowing date and row spacing on yield components and swelling factor of Plantago indica during 2009-10 & 2010-11 at Directorate of Medicinal and Aromatic Plants Research (DMAPR), Anand, Gujarat. Its an endeavour and a step forward to develop Good Agricultural Practices (GAP) in this newly introduced species. In this study, the sowing dates in five levels (30 October, 15 November, 30 November, 15 December and 30 December) and row spacings in six levels (50 × 15 cm, 60 × 15 cm, 65 × 15 cm, 70 × 15 cm, 75 × 15 cm and 80 × 15 cm) were evaluated. Results of experiment revealed that there were significant differences for sowing date and spacing effects on plant height, number of branch per plant, number of spikes per plant, number of grains per plant, biological yield and grain yield. The maximum grain yield belonged to sowing date 15 November and row spacing 50 cm. Maximum number of spikes per plant and grains per plant also belonged to 50 cm row spacing which resulted in increasing grain yield in this row spacing. The results revealed that sowing between 15-30 November is the best time for sowing in P. indica with suitable spacing either at 50 or 60 × 15 cm. However, seeds sown on 30 November showed significantly more swelling (12.0 cc/g) compared to those sown on other dates. Swelling factor varied from 9.0 to 12.0 cc/g. Hence, it can be concluded that the sowing date played an important role on the growth parameters and seed characteristics of Plantago indica. However, swelling factor in this species is a matter of concern which was not much influenced by these factors.